Synthesis and Morphological Control of Mesoporous SiO2 with Cotton as Bio-Template - Lu, Qiuyue; Chen, Zhigang; Chen, Feng; Huang, Xuan; Wu, Zhengying (Asian Journal of Chemistry, 2014)
Mesoporous SiO2 with special short open axis-like morphology was successfully fabricated by using cotton fibers as bio-templates. Mesostructure and morphology of the samples were systematically studied by changing the cotton/SiO2 weight ratio and hydrothermal treating temperature. Textural property and morphology of the obtained mesoporous SiO2 were characterized by the combination of X-ray diffraction, N2 adsorption-desorption experiments and scanning electron microscope. Finally, batch adsorption of methylene blue was performed to detect the adsorption capacity of the cotton co-templated materials.